The effects of using computer in teaching literature component / Faizah Jaafar - Jaafar, Faizah (2006)
This study intends to examine the effectiveness of using computer in teaching literature. In addition, this study was designed to investigate the students’ perceptions towards computer in learning literature. The study employed a quasi-experimental study. There were 46 form four students, 22 males and 26 females, of SMK Seri Nilam, Kuala Terengganu who involved in the study. 23 students were in the control group and another 23 students were in the experimental group. The students in both the control and experimental group were taught a poem, Sonnet 18 and a short story, Lotus Eater during the study. The computer was used as a teaching tool in teaching the experimental group students. The teacher applied power-point presentation in teaching the poem and courseware in teaching short story. However, the students in the control group were taught using the traditional method of chalk and talk. Pretests were administered to both the control and experimental group before the study began. After the teacher had completed teaching each topic, post-tests were given. An independent t-test was conducted on the raw scores of the pretest and it revealed that both groups were found to be equivalent in knowledge of content. The post-tests result indicated that the experimental group whose teacher used computer as a teaching tool performed as well as the control groups whose teacher used traditional method of talk and chalk. The computer did not boost students’ performance in learning literature. The students in the experimental groups were given questionnaires to elicit their perceptions towards using computer in learning literature after they had already sat for their second post-test. The finding revealed that they preferred to learn literature component using computer compared to the traditional way as they found it more interesting and enjoyable. Computer was also found to help them in understanding the lesson better.